Upper and Lower Bounds of Biometric Identification E-Capacity - Haroutunian, Mariam E.; Ter-Vardanyan, Lilit A.; Muradyan, Arthur R. (Mathematical Problems of Computer Science, 2021)
In this paper we introduce a new concept of E-capacity for biometric identification system, which is the generalization of the capacity studied by Willems et al [1]. We investigate this function by constructing upper and lower bounds. When E→0 we derive the lower and upper bounds of the channel capacity which coincides with the capacity obtained in [1].